03453660
prove:
when xz= yz then x=y if z is not equal to zero
Delete
Share
This Question is Closed
ParthKohli
Best Response
You've already chosen the best response.
0
This uses certain axioms.
ParthKohli
Best Response
You've already chosen the best response.
0
Well... this is itself an axiom.
03453660
Best Response
You've already chosen the best response.
0
yes but how to prove
ParthKohli
Best Response
You've already chosen the best response.
0
Divide both sides by \(\rm z\).
03453660
Best Response
You've already chosen the best response.
0
no no i worked like that but it needs another proof
hba
Best Response
You've already chosen the best response.
0
You Mean Geometric Proofs ?
akhilnkumar
Best Response
You've already chosen the best response.
0
@ParthKohli seems right. Dividing both the sides by z is possible only when z is not equal to 0. Cuz, any number divided by 0 is not defined. Do reply if you get another proof.
hba
Best Response
You've already chosen the best response.
0
Take z inverse operation
xz * z^-1 = yz * z^-1
x = y
hba
Best Response
You've already chosen the best response.
0
Well Pk is Right
vipul92
Best Response
You've already chosen the best response.
0
we can write x/y=z/z
so x/y=1
so x=y
03453660
Best Response
You've already chosen the best response.
0
ok man i got the proof wanna share with you guyssssss
as xz = yz -----> given
xz- yz = 0
(x-y)z = 0
as z is not equal to zero-----> given
thus x-y=0
=> x=y
hence proved
thanks to all of you. thanks alot for your time
03453660
Best Response
You've already chosen the best response.
0
@hba ,@vipul92 ,@akhilnkumar ,@ParthKohli